Laparoscopic transposition of lower-pole crossing vessels: Long-term follow-up of 33 patients at puberty. Issue 4 (August 2016) - Madec, François-Xavier; Faraj, Sébastien; Villemagne, Thierry; Fourcade, Laurent; Lardy, Hubert; Leclair, Marc-David
Summary: Purpose: Laparoscopic transposition of lower-pole crossing vessels (LPCV) has been described as an effective alternative to dismembered pyeloplasty in selected indications of hydronephrosis, with purely extrinsic vascular PUJ obstruction. We hypothesized that the initial good results of laparoscopic transposition of LPCV in children presenting with pure extrinsic PUJO were sustained at puberty when these children go through statural growth, without inducing significant changes in systemic arterial blood pressure. Hence, we analysed the long-term follow-up of adolescents successfully treated with this technique during childhood, reviewed after they have reached puberty, focusing on the incidence of recurrent symptoms, renal dilatation, and systemic hypertension. Patients and methods: Early 2015, among a cohort of 70 patients prospectively followed-up since they had undergone laparoscopic transposition of LPCV during childhood (2005–2012), we performed systematic clinical assessment of the 33 adolescent patients (16 years; range 12–22) who had reached puberty age. Assessment focused on clinical examination, arterial blood pressure measurements, and renal ultrasonography (Table). Results: The median delay since surgery was 67 months (31–113 months). Arterial blood pressure adjusted for age and height was within normal range in all patients. Three patients had occasional episodes of abdominal pain: two of them had normal US (including during pain episodes), one had persistent extra-renal dilated pelvis with no calyceal dilatation. None of them showed obvious clinical characteristics linking the pain to a renal origin. Renal US showed residual SFU grade 2 pelvicalyceal dilatation in 2/33 asymptomatic patients; SFU grade 1 extra-renal pelvis dilatation in 3, and was normal in the remaining. When Doppler analysis was performed, there was no evidence of lower-pole parenchyma perfusion defect. Discussion: In adolescents successfully treated during childhood with transposition of LPCV, there seemed to be no impact of this procedure on systemic arterial blood pressure in adolescents after puberty, nor any evidence of late recurrence of symptoms or hydronephrosis. The main limitation of the present study relies in its retrospective nature, the limited sample size, and the obvious difficulty in adequate selection of candidate patients to this technique. The present experience however reinforces the hypothesis that a vast majority of children can be definitely cured with transposition of LPCV when they represent the sole aetiology of obstruction. Conclusion: In the long-term follow-up, most adolescents successfully treated during childhood by laparoscopic transposition of LCPV for PUJ extrinsic obstruction remain asymptomatic, with normal arterial blood pressure, and normal renal ultrasound when they reach puberty. Table 1 Patients characteristics. Patients n = 33 Age at surgery (years) 9.8 (5.9–16.3) Delay since surgery (years) 5.6 (2.6–9.4) Age at assessment (years) 15.8 (12.6–22.8) Arterial blood pressure (z-score) in males Systolic 0.18 ± 1.17 Diastolic 0.29 ± 0.79 Arterial blood pressure (z-score) in females Systolic 0.57 ± 0.82 Diastolic 0.46 ± 0.70 Renal ultrasound pelvis anteroposterior diameter (mm) Preoperative 33 (16–60) Postoperative (1 year) 8.5 (4–14) Postoperative (last follow-up) 9 (4–31) Quantitative values expressed as median (range). z-Score of arterial blood pressure compared with international norms, adjusted for gender, age, and height.